Disembodied Vocal Innocence: John Addington Symonds, the Victorian Chorister, and Queer Musical Consumption - Riddell, Fraser (Victorian Literature and Culture, 2025)
In the early 1890s, both John Addington Symonds and Arthur Symons were fascinated by Paul Verlaine's sonnet “Parsifal” (1886)—in particular, by its final line, which dwells on the voices of singing children. Symonds enthused to Symons that it was “a line [to] treasure forever,” while, nevertheless, noting his reservations to Horatio Forbes Brown that “fine as it is, [it] looks like it […] must be rather of the sickly school.” In an article on Verlaine, Symons praised the poem as a “triumph [of] amazing virtuosity,” echoing the sentiments of his friend George Moore, who in Confessions of a Young Man (1886) exclaimed that he “kn[ew] of no more perfect thing than this sonnet.” With its repetition of assonant vowel sounds, Verlaine's closing line captures the gentle rise heavenward of the ethereal voices of Richard Wagner's offstage choristers, resounding above the stage at the conclusion of the opera. The hiatus with which the line opens functions as a sigh of renunciation, as the listeners abandon themselves to the inexpressible force of the transcendent. In Verlaine's sonnet, these children's voices become the epitome of the “disembodied voice” that Symons sees as so characteristic of Decadent poetics. They sing of the delicate immateriality of spiritual experience, the transient fragility of existence.
EPrint Processing Status: Full text deposited in DRO